Differential diagnosis of Drave's syndrome and Gasto's Lenox syndrome on the example of a clinical case - Raushan Kenzhegulova; Alisa Nauryzbaeva; Assem Khamzina (National Scientific Medical Center, 2017)
Presented a case of Drave's and Gasto's Lenox syndromes in a 10-years old patient. Provided differential diagnosis and discussed treatment options.